Papers on Quintilian and ancient declamation - Winterbottom, Michael 1934- (Oxford University Press, 2019)
Declamation - the practice of training young men to speak in public by setting them to compose and deliver speeches on fictional legal cases - was central to the Greek and Roman educational systems over many centuries and has been the subject of a recent explosion of scholarly interest. The work of Michael Winterbottom has been seminal in this regard, and the present volume brings together a broad selection of his scholarly articles and reviews published since 1964,0creating an authoritative and accessible resource for this burgeoning field of study. 0The assembled papers focus on two related topics: the rhetorician Quintilian and ancient declamation in practice. Quintilian, who taught rhetoric at Rome in the second half of the first century AD, was the author of the Institutio Oratoria, a key text for Roman educational practice, rhetoric, and literary criticism. Subjects explored in the present collection range widely over not only the establishment and interpretation of the text and its literary and historical context, but also Quintilian's views on inspiration, morality, philosophy, and declamation, of which he was a practitioner. While the volume also offers detailed examinations of the texts and interpretations of a wide range of Latin and Greek authors of declamations, such as Seneca the Elder, Sopatros, and Ennodius, there is a particular focus on two collections wrongly attributed to Quintilian, the so-called 'Minor' and 'Major Declamations'. A major re-assessment of the manuscript tradition of the latter collection is published here for the first time
Keywords: Quintilianus, Marcus Fabius -- 35-100; Rhetorik; Quintilian / Criticism and interpretation; Rhetoric, Ancient